Vocational education memories: meanings and sensibilities in the early religious life at the Congregation of the Sisters Servants of the Immaculate Conception (1960-1990) (Revista Tempo e Argumento, 2020)
This article aims to discuss various aspects of female religious vocational education from the perspective of sensibility and discipline. To do this, we bring testimonies of women who underwent the vocational education process at the Congregation of the Sisters Servants of the Immaculate Conception. The utterances, in dialogue with professional education handbooks, build a rather large panorama, which makes it possible to glimpse the construction of meanings and vocations for later work institutionally linked to the Catholic Church